A statistical analysis and comparison of the fine structures of the ion upflow associated with the double-peak subauroral ion drift - Zhang, Qiang; Han, De-Sheng; Teng, Shang-Chun; Wang, Zhi-Wei; Zhang, Q.-H.; Xing, Zan-Yang; Wang, Yong; Ma, Yu-Zhang (Frontiers in Astronomy and Space Sciences, 2023)
The ion upflow associated with the subauroral ion drift (SAID) is a crucial component in the exchange of particles between the ionosphere and the ring currents. The ion upflow associated with the double-peak subauroral ion drift (DSAID), which is a subclass of the SAID, is more complex compared to SAID. In this study, we conducted a statistical analysis of the ion upflow associated with DSAID using Defense Meteorological Satellite Program (DMSP) F16–F18 data spanning 11 years (2010–2020) in the Northern Hemisphere. Our findings revealed that ion upflow associated with DSAID can exhibit either a double-peak or a one-peak upflow. The statistical characteristics of these two types of events displayed significant differences. In DSAID with a double-peak upflow event, the velocity of DSAID around the high-latitude peak was greater than that around the low-latitude peak. However, in DSAID with a one-peak upflow event, the DSAID velocities around the two peaks were very similar. Based on the formation mechanism of DSAID and the process of frictional heating in the ionosphere, we proposed that the formation of DSAID with a double-peak upflow and DSAID with a one-peak upflow are likely related to the formation process of DSAID.